REVIEW OF ISLAMIC LAW ON THE BUYING AND BUYING OF FOOD BY STREET VENDORS - Yuyun Suhairo Ritonga; M. Yarham (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
Buying and selling is an exchange of ownership of objects with the exchange, according to the form permitted by sharia. The application of buying and selling ethics in Islam must be applied in all aspects of the economy, including consumer knowledge regarding the halalness of the products they will consume. The beginning of this research is determining the Islamic law review of buying and selling food at street vendors in the Sadabuan complex. This research method uses descriptive qualitative methods, and the type of use is field data research. Data collection techniques include data reduction, data integration and conclusion. These results and research. The majority of street vendors in the Sadabuan complex still need to get a reviewed business license. According to Islamic law, humans are allowed to carry out any business or buying and selling transactions to fulfil their daily needs. Meanwhile, ownership of a business license is not legally obligatory because it is not a condition for buying and selling transactions in the Islamic context.